2010
DOI: 10.1007/s00436-010-2010-z
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic activity of steroidal saponins from Dioscorea zingiberensis C. H. Wright against Dactylogyrus intermedius (Monogenea) in goldfish (Carassius auratus)

Abstract: Dactylogyrus intermedius is one of the most pathogenic monogenean parasites on the gills of captive fish and can cause serious problem in aquaculture. To attempt controlling this parasite and explore novel potential antiparasitic agents, the present study was designed to investigate the anthelmintic activity of Dioscorea zingiberensis C. H. Wright against D. intermedius in goldfish under in vivo conditions. Bioactivity-guided fractionation and isolation of the compounds responsible for anthelmintic activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 25 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…The current work in our laboratory is focused on screening medicinal plants with promising anthelmintic activity and isolating groups of compounds/pure compounds responsible for the activity. We have previously reported that crude extracts of several traditional medicinal plants, such as Arctium lappa L., Dioscorea zingiberensis C. H. Wright, Paris polyphylla, Angelica pubescens, Dryopteris crassirhizoma, and Cimicifuga foetida L. (Wang et al 2009a(Wang et al , 2010aLiu et al 2010;Lu et al 2011;Wu et al 2011) and some bioactive compounds, including arctigenin, trillin, gracillin, and dioscin (Wang et al 2009a(Wang et al , b, 2010b can effectively control the D. intermedius infection in goldfish (Carassius auratus). This study screened 42 kinds of medicinal plants for anthelmintic activity against D. intermedius in goldfish (C. auratus).…”
Section: Introductionmentioning
confidence: 98%
“…The current work in our laboratory is focused on screening medicinal plants with promising anthelmintic activity and isolating groups of compounds/pure compounds responsible for the activity. We have previously reported that crude extracts of several traditional medicinal plants, such as Arctium lappa L., Dioscorea zingiberensis C. H. Wright, Paris polyphylla, Angelica pubescens, Dryopteris crassirhizoma, and Cimicifuga foetida L. (Wang et al 2009a(Wang et al , 2010aLiu et al 2010;Lu et al 2011;Wu et al 2011) and some bioactive compounds, including arctigenin, trillin, gracillin, and dioscin (Wang et al 2009a(Wang et al , b, 2010b can effectively control the D. intermedius infection in goldfish (Carassius auratus). This study screened 42 kinds of medicinal plants for anthelmintic activity against D. intermedius in goldfish (C. auratus).…”
Section: Introductionmentioning
confidence: 98%
“…These parasites are egg layers with two to four eyespots and one pair of large anchor hooks, and have a direct life cycle without intermediate host (Wang et al 2010a). Their life cycle comprises an obligate adult stage, fertilized egg, and free-swimming larvae stage.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increased research activities have been demonstrated on the utilization of plant extracts to treat parasitic diseases in animals, including fish (Madsen et al 2000;Paolini et al 2003;Zahir et al 2009;Wang et al 2009Wang et al , 2010. Buchmann et al (2003) reported raw extracts from garlic (Allium sativum) were used to treat I. multifiliis infestation by killing theronts and tomonts.…”
Section: Introductionmentioning
confidence: 99%